Executive Committee Minutes 2011-05-12 - Academic Senate:::::::::
Chair Report. Minutes of 4/28/11 – Approved. Agenda – Approved. President Report. CCJS revision, Psychology MA revision and Counseling MA revisions all approved for Senate consent calendar. Update from Standing Committees on President's Diversity Council letter – FSAC and SAC reporting. Statewide Senator Report. Vice President of SAEM Report. APC Report. EPC Report. FSAC Report. SAC Report. CFA Report. Associated Students Report. Senate Agenda approved. Good of the Order.